Amniotic Membrane Transplantation in Surgical Treatment of Conjunctival Melanoma: Long-term Results - Melis Palamar; Banu Yaman; Taner Akalın; Ayse Yağcı (Türk Oftalmoloji Dergisi, 2018)
Objectives: To investigate the long-term efficacy and results of surgical management of conjunctival melanoma reconstructed with amniotic membrane transplantation. Materials and Methods: Conjunctival melanoma in 10 patients (5 female, 5 male) was totally excised with adjunctive cryotherapy to the surgical margins, corneal epitheliectomy with absolute alcohol in cases of corneal involvement, lamellar sclerectomy in cases with episcleral involvement, and ocular surface grafting with cryopreserved amniotic membrane. Complications and tumor control rates were evaluated. Results: The mean age of the patients was 57.4±15.2 (range, 37-84) years. The mean diameter of the tumors was 15.5±4.9 (range, 10-25) mm and histopathologically confirmed complete excision was performed in all cases. Mild limbal stem cell deficiency (2 eyes) and subclinical symblepharon (3 eyes) were observed as long-term complications. In a mean follow-up of 56.7±40.4 (range, 30-132) months, only one local tumor recurrence was detected. Despite retreatment, exenteration was performed in this patient due to re-recurrence. One patient died due to disseminated metastasis despite the absence of local recurrence. Conclusion: In large conjunctival melanomas, reconstruction of the ocular surface is usually very challenging. The use of cryopreserved amniotic membrane for conjunctival defect repair is safe and effective with mild complications, and allows the excision of wider margins around the tumor.